Initial Reports of the Deep Sea Drilling Project 1985
DOI: 10.2973/dsdp.proc.83.115.1985
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry of Hot Waters Sampled from Basaltic Basement in Hole 504B, Deep Sea Drilling Project Leg 83, Costa Rica Rift

Abstract: Seawater that has been altered by reaction with basaltic basement has been sampled from Deep Sea Drilling Project Hole 504B, located on 5.9-m.y.-old crust on the southern flank of the Costa Rica Rift. Fourteen water samples have been collected on Legs 69, 70, and 83, both before and after renewed drilling on the latter two legs, at temperatures from 69 to 133°C and pressures from 390 to 425 bars.The water sampled prior to renewed drilling on Leg 83 had occupied the hole for nearly 2 yr. since it was last flush… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0

Year Published

1986
1986
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(44 citation statements)
references
References 19 publications
2
42
0
Order By: Relevance
“…More direct inferences about the nature of formation waters were made possible during Legs 69, 70, and 83, when water samples were acquired with a go-devil-packer sampler working in both active and inactive modes (Mottl, Anderson, et al, 1983;Mottl et al, 1985). The studies carried out during Leg 83 indicated that large changes in the composition of the borehole waters had taken place after surface seawater was introduced into the hole during Leg 70 (about 2 yr. before).…”
Section: Introductionmentioning
confidence: 99%
“…More direct inferences about the nature of formation waters were made possible during Legs 69, 70, and 83, when water samples were acquired with a go-devil-packer sampler working in both active and inactive modes (Mottl, Anderson, et al, 1983;Mottl et al, 1985). The studies carried out during Leg 83 indicated that large changes in the composition of the borehole waters had taken place after surface seawater was introduced into the hole during Leg 70 (about 2 yr. before).…”
Section: Introductionmentioning
confidence: 99%
“…While experimental evidence suggests that hot-spring Sr is released only during high-temperature diabase alteration (Berndt, Seyfried, and Beck, 1988), numerous studies on sub-seafloor pore waters show that basaltic Sr is also released during low-temperature alteration (Mottl and others, 1985;Mottl and Gieskes, 1990;Hess, Bender, and Schilling, 1991). Moreover, there is evidence that warm (ϳ60°C) and intermediate-temperature (ϳ250°C) hot springs may be important along oceanic ridges (Mottl and others, 1998;Teagle, Alt, and Halliday, 1998); these may also carry considerable amounts of Sr.…”
mentioning
confidence: 99%
“…As no obstructions were encountered, no rotation or circulation was required, and the fluid samples and temperature measurements were generally good (Mottl et al, 1983(Mottl et al, , 1985Gieskes et al, 1986;Becker et al, 1983aBecker et al, , 1983b. When Leg 111 reentered Hole 504B, no hole problems were expected, and the initial reentry was made with a lightweight French temperature logging tool, which was run to within 55 m of hole bottom, followed by several runs of Kuster water samplers and a Schlumberger water sampler.…”
Section: Operational Considerations For Sampling Borehole Fluidsmentioning
confidence: 99%
“…The WSTP and Kuster tools are described as "passive" samplers (Mottl et al, 1983(Mottl et al, , 1985 was run in Hole 504B as the primary sampling tool to extract a pore-fluid sample from the wall of the borehole. The RFT is a "doughnut" sampler run on the logging line, with a circular sealing port that is pressed against the side of the borehole using a mechanical arm.…”
Section: "Active" Fluid Samplingmentioning
confidence: 99%